Pregnancy, childbirth and neonatal outcomes in women with inherited bleeding disorders: A retrospective analysis. (10th March 2022) - Clarke, Lisa; Curnow, Jennifer; Cutts, Briony; Ross, Bryony; Kidson‐Gerber, Giselle
Tweetable abstract: Women with inherited bleeding disorders can deliver without complication when best practices are maintained. Abstract: Objective: To describe the characteristics and outcomes of women with inherited bleeding disorder during pregnancy and birth. Design: Retrospective cohort study. Setting: Tertiary care hospitals, New South Wales and Victoria, Australia. Population: One hundred women with inherited bleeding disorders, who birthed 134 live infants from 132 pregnancies. Methods: Data were retrospectively obtained from the patient and neonatal medical records. Descriptive analysis was used to report maternal and pregnancy characteristics and birth and neonatal outcomes. Main outcome measures: Factor replacement, neuraxial analgesia use and complications, postpartum haemorrhage (PPH) and neonatal complications. Results: PPH occurred in 22% of deliveries with primary PPH occurring in 20% and secondary PPH in 2% of births; 48% of PPH were classified as major. PPH occurred across the spectrum of inherited bleeding disorders and was evenly distributed between women who had 'normalised' (46%) their factor levels in pregnancy compared with those requiring factor at the time of birth (50%). An obstetric cause was identified in almost half of PPH (46%). Neuraxial analgesia was administered in 40% of births without complication and refused in 3% of births despite documented adequate haemostatic potential. Conclusions: Women with inherited bleeding disorders can deliver safely and receive neuraxial analgesia without complication when best practices are adhered to. PPH appears to occur at higher rates than in the general population despite adequate factor levels or planned replacement. Although an obstetric cause was demonstrable in the many cases, these findings raise concern over the current definition of 'adequate' factor levels at the time of birth. Tweetable abstract: Women with inherited bleeding disorders can deliver without complication when best practices are maintained.